The impact of tax knowledge and budget spending influence on tax compliance - Behnud Mir Djawadi; René Fahr (Institute for the Study of Labor (IZA), 2013)
We investigate the impact of trust in authorities on tax compliance within a controlled laboratory setting. Embedded in two hypothetical tax systems with high and low power of authorities respectively, we gradually increase trust in authorities in form of tax knowledge about public expenditures and by allowing taxpayers to decide on what public goods they want their tax dollars to be spend for. To clearly disentangle any effects from factors that are known to influence tax compliance from previous studies, we control for tax commitment, risk attitude, income and effort exerted to earn the income which the taxpayers report truthfully or underreport to the tax authority. Non-parametric statistical analyses as well as multivariate regressions provide clear evidence that tax compliance is higher in tax systems with low power of authorities when providing complete transparency on public expenditures and when taxpayers are given the possibility to decide on the use of their taxes. With a powerful tax authority in place which is reflected in high audit rates, compliance does not change when increasing trust in authorities. Our results have important policy implications as the mere hypothetical possibility to express preferences on budget spending influences tax compliance.
Keywords: H26; C91; 330; tax evasion; tax compliance; tax knowledge; budget spending; real effort; experimental economics